Calculation method for holding prestress of corroded prestressed anchor cable in long-term operation slope - Yang, Zhao; Nie, Biao; Xie, Yining; Li, Hongwen; Chen, Song; Zhang, Qingqing; Tian, Qingyan; Lin, Sen; Yuan, Ying (Frontiers in Materials, 2023)
Due to the rich water in the weathered layer of the free section, the prestressed anchor cable of the long-term operating slope is severely corroded and its mechanical properties are deteriorated, affecting the stability of the slope. Based on a certain number of long-term operation highway anchor cable excavation tests, the author found that the free section of the anchor cable orifice was seriously corroded.Currently, there is very little research on the relationship between the holding capacity of anchor cables and the degree of corrosion of the free section of the cable, and the research is mainly focused on the life of the anchor section. Therefore, the constitutive relationship of the cable body is established on the basis of corrosion force coupled statistical damage mechanics, and the relationship between the degree of corrosion of the cable body and the holding prestress of the operating slope anchor cables is derived using the load transfer method. The rationality of prestressed anchor cables on highway slopes during the operation period was verified by actual measurement. This study has positive significance for long-term stability analysis of slopes.